Integrating Technology and Social Media to Foster Language Learner Autonomy: Students’Perception (مجلة العلوم الشاملة, 2024)
The incorporation of technology and social networking sites (SNSs) is steadily gaining popularity among EFL students, due to the capacity to provide learners with opportunities to create profiles, interact in authentic ways with their peers, and forge relationships (Thorne, 2010). Thus, university students utilise diverse social media platforms and approaches which enhance and strengthen their learningthrough reflection and collaborative activities in virtual environments (Armstrong & Franklin, 2008). In fact, such SNSs can increase students’ motivation, and promote the management of autonomous learning (Ushioda, 2006; Thorne, 2003; Ware, 2005).As language teachers play a pivotal role in improving learner autonomy andadvancing learner responsibility for personal language learning, they must adopt the role of facilitator and create a suitable environment that helps learners to be responsible for their learning, rather than being mere authority figures.Social media have various positive benefits for students’ learning (Hwang, Kessler, & Francesco, 2004). In addition to ease of access, social media platforms foster improvements in student communications and language skills via multiple forms of interactive media which facilitate user interaction through the Internet.As SNSs users increasingly availed of the advances and facilities that social media provide, the present study aims to evaluate learners’ readiness and self-governance, and the extent to which social media tools promote learners’ English language autonomy. In order to do so, a survey of 30 SubratahUniversity in Libya participants was conducted to identify current student perceptions of learner autonomy and technology in language learning. The findings confirmed that Libyan university students place a high value on the significance of social media as a means to improve their English language skills and demonstrated a pronounced trend towards autonomous learning to learn English outside the classroom.